Blood Condition of (Clarias batrachus) from the Tapung Kiri and Sail Rivers Riau Province - Pratiwi, Via Anggraini; Eddiwan, Eddiwan; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Clarias batrachus is a freshwater fish that inhabit the Tapung Kiri and Sail Rivers. The water quality in the Tapung Kiri River is relatively good, while that of the Sail River is polluted. As the water quality in general affects the blood condition of the fish, it is predicted that blood condition of C. batrachus from the Tapung Kiri and Sail Rivers are different. A research aims to understand the blood condition ofC. batrachus from those rivers were conducted from February-March 2019.There were 12 fishes captured from each river. The fish blood was taken and then analyzed for the number of erythrocytes, leukocytes, hematocrit and leucocrite levels and the type of leukocyte was identified. Results shown that the number of erythrocytes, leucocyte, haematocrite and leuoccrite levels of the fish from the TapungKiri River was 2,160,000 cells/mm3, 200,833cells/mm3, 32.96% and 1.71% respectively. While those of the Sail River was 2,121,667 cells/mm3, 211,375 cells/mm3, 31.27% and 1.81% respetively. There were six types of leukocytes present in the blood of fish from both areas. In the fish from the Tapung Kiri River, there were eosinophil (5.7%),lymphocytes (72.1%), monocytes (3.6%),neutrophils (2.6%) and thrombocytes (16.0%). While in the fish from the Sail River, there were eosinophil (6.4%),lymphocytes (43.2%), monocytes (20.3%),neutrophils (6.9%)and thrombocytes (23.2%).Based on the data obtained it can be concluded that the condition of fish from the Tapung River is healthy and the fish from Sail River is unhealthy. Keywords: erythrocytes,leukocyte,haematocrite, leucocrite